Screening of date palm varieties against lesser date moth Batrachedra amydraula Myer on date palm (Phoenix dactylifera L.) in semi-arid region of Rajasthan - S.K. Yadav; B.D.S. Nathawat; Rajendra Singh Rathore (Annals of Agricultural Research, 2025)
The studies on screening of different date palm varieties were conducted at date palm research center, SKRAU, Bikaner in semi-arid region of Rajasthan from 2018 to 2022. Thirty-four varieties of date palm were screened for their relative susceptibility against lesser date moth for five consecutive years. The minimum infestation of lesser date moth was recorded on Agloni, Amri, Umshok, Sakloti and Medini varieties. While Barhee, Medjool, Nagal, Halawy and Khuneizi showed maximum per cent fruit infestation against lesser date moth and these varieties were categorized as highly susceptible. The other varieties i.e., Migraf, Suria, Hayani, Sedami, Bint-a-isha, Zagloul, Shamran, Abdul Rehman, Barshi, Tayar, Muscat, Hatemi, Hamra, Sewi, Sri Ganganagar, Zahidi, Gizaz, Ruziz, Khadrawy, Bikaner, Khasab, NagalHilali, Sayar and Khalas were ranked as moderately susceptible varieties.